A potential method to determine pigment particle size on ancient murals using laser induced breakdown spectroscopy and chemometric analysis. Issue 11 (2nd March 2021) - Yin, Yaopeng; Yu, Zongren; Sun, Duixiong; Su, Maogen; Wang, Zhuo; Shan, Zhongwei; Han, Weiwei; Su, Bomin; Dong, Chenzhong
Abstract : Information on pigment sizes in murals is a key factor in determining the suitable processes of possible restoration and conservation on ancient murals and is also significant for the investigation of a mural's historic value and analysis of its technical process. Abstract : Information on pigment sizes in mural samples is a key factor in determining the suitable processes of possible restoration and conservation on ancient murals and is also significant for the investigation of a mural's historic value and analysis of its technical process. Thus, in this paper, the green painted layers composed of different pigment sizes were analyzed by laser-induced breakdown spectroscopy. First, a parametric study was undertaken to optimize the LIBS signal to noise ratio and decrease fluctuations. Then, the variation of LIBS signal with pigment size was studied on simulated mural samples. Finally, a classifiable model of pigment sizes was built by coupling with the PCA method and was successfully applied to classify pigment sizes on real mural pieces.